The First Investigation of West Nile Virus in Horses Using Real Time RT-PCR in Middle Black Sea Region in Turkey - Zafer Yazici; Harun Albayrak; Emre Ozan; Semra Gumusova (Tehran University of Medical Sciences, 2015)
Background: West Nile Virus (WNV) is a mosquito-borne disease that can cause fatal infection in mammals in-cluding humans, dogs, horses, birds and reptiles. Although West Nile Virus is an asymptomatic infection, especially it can cause neurologic disorders in humans and horses. The aim of this study was to the investigate virological pres- ence of WNV in horses in the Black Sea Region of Turkey using real time RT-PCR (rRT-PCR). Methods: Totally, 120 horse sera were collected equally from 4 provinces in Middle Black Sea Region of Turkey and investigated for WNV presence by Taqman based rRT-PCR. Results: WNV nucleic acid was not detected in any horse serum sample. Conclusion:  Although obtained result indicated no evidence of WNV-RNA in horses, Black Sea Region of Turkey is one of the suitable places for the WNV infection. For this reason, our research will continue for the determination of the viruses in vectors and susceptible animals such as horses, dogs, etc.